PERANAN DAN SUMBANGAN NIK RAHIMAH NIK IDRIS DALAM BIDANG SULAMAN KELINGKAN: THE ROLE AND CONTRIBUTION OF NIK RAHIMAH NIK IDRIS IN ‘KELINGKAN’: A MALAY TRADITIONAL EMBROIDERY - Ab. Rahman, Norhayati; Abdul Majid, Maizira (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract The ‘kelingkan’ embroidery is a traditional Malay art passed on from generation to generation. The art received the highest recognition from female nobility and aristocrats who wore it to important events in olden times. However, the art of embroidering ‘kelingkan’ faces extinction due to a decrease in demand from the community because of its high cost and shortage of skilled ‘kelingkan’ embroiderers. Moreover, there is a lack of reference materials and documentation of ‘kelingkan’; hence it is not widely known today. This paper, therefore, aimed to introduce a prominent ‘kelingkan’ practitioner from Kelantan named Nik Rahimah Nik Idris. The research delved into her role and contribution towards ‘kelingkan’ embroidery, specifically in Kelantan and Malaysia in general. Researchers conducted a literature review and then fieldwork to interview ‘kelingkan’ embroiderers. The results were then evaluated through content analysis. Findings showed that Nik Rahimah is indeed an important figure in the art of ‘kelingkan’ as she was a royal embroiderer, ‘kelingkan’ demonstrator, expert and promoter of the art in Malaysia and abroad. As such, she has made a significant contribution in upholding and preserving the art of ‘kelingkan’ embroidery. Keywords: role, embroiderer, kelingkan, Kelantan.